The Effectiveness of Scientific Approach in Enhancing Short Story Writing Skills: A Quasi-Experimental Study at an Islamic Boarding School - Jalaluddin, Muhammad; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
This study aims to analyze the effectiveness of the scientific approach in improving the short story writing ability of grade IX students at MTs Pondok Pesantren Mawaridussalam, Deli Serdang Regency. The scientific approach consists of five main stages, namely observing, asking, collecting information, reasoning, and communicating. The main problem raised in this study is the low short story writing skills of students due to less interactive learning methods and less opportunities for exploration for students. The research method used is a quasi-experimental with a pretest-posttest control group design. The research sample consisted of 72 students divided into two classes, namely the experimental class that applies a scientific approach and the control class that uses the Contextual Teaching and Learning (CTL) approach. Data were collected through short story writing tests before and after treatment, and analyzed using a t-test to test differences in learning outcomes for the two groups. The results showed that there was a significant increase in short story writing skills in the experimental class compared to the control class. The average posttest score of students in the experimental class was 84.91 with a variance of 31.33, while in the control class it only reached 73.03 with a variance of 18.54. The results of the t-test showed that t count 2.03> t table 1.99, which means that the use of a scientific approach has a significant effect on improving students' short story writing skills. The conclusion of this study is that the scientific approach is more effective than the CTL approach in improving students' short story writing skills. Therefore, it is recommended that teachers apply the scientific approach in learning to write short stories in order to improve students' creativity and understanding of the structure and techniques of writing short stories